Measuring Grit Gen Z: Adaptation and psychometric properties of Grit-O Indonesian version - Arina Nur Hikmah; Rosita Endang Kusmaryani; Herwin Herwin; Tanesh N Segar (Proyeksi, 2026)
Grit defined as persistence and passion for achieving long-term goals, has received increasing attention in psychology research due to its association with academic achievement, career, and resilience. Although the Grit-O Scale developed by Angela Duckworth (2007) has been widely used internationally, validated instruments for measuring grit in Indonesian cultural and linguistic contexts are still limited. Therefore, adapting and examining the psychometric properties of such scales is important to ensure their suitability for research and assessment in Indonesia. This research aims to adapt the Grit-O Scale of Angela Duckworth (2007) into the context of Indonesian culture and language. The study involved 153 respondents between the ages of 18 and over 28. The adaptation process is carried out through several stages: (1) translation, (2) synthesis, (3) back translate, (4) readability test, and (5) finalization. Reliability testing was performed using Omega McDonald and stratified alpha composites, while construct validity was checked using confirmatory factor analysis (CFA). The results showed that the adapted scale showed high reliability, with a value of 0.850, and a validity indicating good two-factor model conformity, with RMSEA = 0.043, CFI = 0.990, SRMR = 0.068, and TLI = 0.987. These findings provide preliminary evidence that the Indonesian version of the Grit-O Scale demonstrates acceptable reliability and validity for use in the Indonesian context.